Endothelial nitric oxide suppresses action-potential-like transient spikes and vasospasm in small resistance arteries - Smith, JF; Lemmey, HAL; Borisova, L; Hiley, CR; Dora, KA; Garland, C (American Heart Association, 2020)
Endothelial dysfunction in small arteries is a ubiquitous, early feature of cardiovascular disease, including hypertension. Dysfunction reflects reduced bioavailability of endothelium-derived nitric oxide (NO) and depressed endothelium-dependent hyperpolarization that enhances vasoreactivity. We measured smooth muscle membrane potential and tension, smooth muscle calcium, and used real-time quantitative polymerase chain reaction in small arteries and isolated tubes of endothelium to investigate how dysfunction enhances vasoreactivity. Rat nonmyogenic mesenteric resistance arteries developed vasomotion to micromolar phenylephrine (α1-adrenoceptor agonist); symmetrical vasoconstrictor oscillations mediated by L-type voltage-gated Ca2+ channels (VGCCs). Inhibiting NO synthesis abolished vasomotion so nanomolar phenylephrine now stimulated rapid, transient depolarizing spikes in the smooth muscle associated with chaotic vasomotion/vasospasm. Endothelium-dependent hyperpolarization block also enabled phenylephrine-vasospasm but without spikes or chaotic vasomotion. Depolarizing spikes were Ca2+-based and abolished by either T-type or L-type VGCCs blockers with depressed vasoconstriction. Removing NO also enabled transient spikes/vasoconstriction to Bay K-8644 (L-type VGCC activator). However, these were abolished by the L-type VGCC blocker nifedipine but not T-type VGCC block. Phenylephrine also initiated T-type VGCC-transient spikes and enhanced vasoconstriction after NO loss in nonmyogenic arteries from spontaneously hypertensive rats. In contrast to mesenteric arteries, myogenic coronary arteries displayed transient spikes and further vasoconstriction spontaneously on loss of NO. T-type VGCC block abolished these spikes and additional vasoconstriction but not myogenic tone. Therefore, in myogenic and nonmyogenic small arteries, reduced NO bioavailability engages T-type VGCCs, triggering transient depolarizing spikes in normally quiescent vascular smooth muscle to cause vasospasm. T-type block may offer a means to suppress vasospasm without inhibiting myogenic tone mediated by L-type VGCCs.